Chemical reageants management in laboratories of the Universidad Nacional - Mora Barrantes, José Carlos (2013)
During years 2008-2009, a diagnostic regarding chemical reagents management (aspects related with; regulations, safety procedures, handle and storage conditions, etc) in teaching and research laboratories of the Universidad Nacional, was carried out. In order to collect such information different strategies/methodologies were used: 1) application of an interview and questionnaire to the laboratories’ personnel, 2)an inspection of the laboratories, 3) generation of chemical reagents database 4) work sessions with university management authorities and 5) interview with chemical products management personnel of public and private institutions .This study allowed to identify the actual conditions for the chemical reagents management at Universidad Nacional, for example; the different procedures for the segregation, storage, labeling and use of the chemicals, as well as the aspects related with; chemical database generation, material and safety equipment control, use of safety procedures, etc. Also, the study allowed to evaluate the existing management procedures executed by university authorities for handling them appropriately. As a conclusion, in order to conduct an adequate chemical reagents management at Universidad Nacional it is necessary to formulate and implement regulation (institutional procedures, protocols, etc) and the establishment of an university office in charge of all the chemical reagents management activities and procedures. Also is necessary to generate national regulations focused on university activities (chemical reagents management) as well as the existing for the industry chemical products control and regulation.